2000
DOI: 10.1111/j.1365-2621.2000.tb10274.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Process Conditions on the Physical and Sensory Properties of Extruded Oat‐Corn Puff

Abstract: The effect of processing variables, including screw speed (200, 300, and 400 rpm), moisture content (18, 19.5, and 21%), and four different percentages (55, 70, 85, and 100%) of oat flour, on the extrudate physical properties (expansion, bulk density, and texture profiles) and sensory properties were studied. Increasing the percentage of oat flour resulted in extrudates with a lower specific length, higher bulk density, lower lightness, higher redness, lower yellowness, higher hardness, and lower springiness, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
141
2
15

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(177 citation statements)
references
References 12 publications
19
141
2
15
Order By: Relevance
“…Ding et al (2006) also reported rapid increase in lateral expansion with the increase in barrel temperature which may be due to higher degree of superheating of water in the extruder encountering bubble formation. The increase in FMC and BR reduces the friction between the feed material, screw and barrel and also has a negative effect on the starch gelatinization and consequently reduces product expansion (Liu et al 2000). Tang and Ding (1994) also reported reduced expansion ratio due to increase in fibre content in feed.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Ding et al (2006) also reported rapid increase in lateral expansion with the increase in barrel temperature which may be due to higher degree of superheating of water in the extruder encountering bubble formation. The increase in FMC and BR reduces the friction between the feed material, screw and barrel and also has a negative effect on the starch gelatinization and consequently reduces product expansion (Liu et al 2000). Tang and Ding (1994) also reported reduced expansion ratio due to increase in fibre content in feed.…”
Section: Resultsmentioning
confidence: 94%
“…Similarly Altan et al (2008a) also reported decrease in PF with increase in BT for snack foods from barley-tomato pomace blends. Liu et al (2000) reported that increase in FMC reduced expansion and provided a dense product that required higher force to break the sample. Sacchetti et al (2005) reported direct correlation between hardness and density of extruded cereal blend, better expansion results in more friable product that requires less force/energy to break.…”
Section: Effect Of Extrusion Cooking On Textural Properties Of Extrudmentioning
confidence: 99%
“…Among several technologies for production of SF, extrusion is highly efficient and versatile in terms of differentiation in texture and size of SF. The physical properties and sensory attributes of extruded products are generally influenced by large number of process variables, of which the amount and structure of starch and protein, and their interaction in native form and during processing are of primary importance (Liu et al, 2000). Parameters such as degree and extent of gelatinization (leading to partial or complete destruction of the crystalline structure), shear induced molecular fragmentation of starch polymers, denaturation of protein are known to affect the quality of extruded SF (Harper, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…Sensory attributes were evaluated by panelists according to Liu et al 2000;Bourne 2002. Evaluation was done under normal white fluorescent lighting at temperature of 22±1°C.…”
Section: Sensory Evaluationmentioning
confidence: 99%
“…Literature review shows that there have been many researches into the textural quality of different kinds of snacks (Katz and Labuza 1981;Halek et al 1989;Liu et al 2000;Pamies et al 2000;Rampersad et al 2003;Veronica et al 2006;Ainsworth et al 2007;Ravi et al 2007;Nath and Chattopadhyay 2008;Greve et al 2010;Lazou and Krokida 2010). However, to our knowledge, there is no or little study available concerning the effects of different combinations of time and temperature of deep-fat frying on sensory and textural properties of pellet snacks.…”
Section: Introductionmentioning
confidence: 99%